Community Based Tourism in the Development of Peneleh Heritage Tourism Village in Surabaya City - Kharisma Eka Deviyanti; Susi Hardjati (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
The city of Surabaya is one of the regions in East Java Province that is rich in tourism potential. From natural attractions to heritage sites, this region has it all. One of them is Peneleh Heritage Tourism Village. Development efforts continue to be directed at developing tourist attractions, increasing promotional activities, and increasing community participation. However, the government's efforts to continue developing Peneleh Heritage Tourism Village have not gone as expected due to low community participation in the tourism management community. Therefore, the community based tourism approach needs attention because this concept actively involves the community as part of the tourism management community. The purpose of this study is to realize community based tourism in the development of Peneleh Heritage Tourism Village in Surabaya. This study uses a qualitative descriptive method with data collection techniques using observation, interviews, and documentation. The results of the study show that the implementation of community based tourism in the development of Peneleh Heritage Tourism Village has had a positive impact on the community, namely an increase in the pride of the tourism management group and the surrounding community in Peneleh to be able to participate in every tourist activity in Peneleh Village to support the sustainability of tourism village development, Even tough all member of the community ar not able to participate.